Highly differentiated soil bacterial communities in Victoria Land macro-areas (Antarctica). Issue 7 (21st June 2021) - Severgnini, Marco; Canini, Fabiana; Consolandi, Clarissa; Camboni, Tania; Paolo D'Acqui, Luigi; Mascalchi, Cristina; Ventura, Stefano; Zucconi, Laura
ABSTRACT: Ice-free areas of Victoria Land, in Antarctica, are characterized by different terrestrial ecosystems, that are dominated by microorganisms supporting highly adapted communities. Despite the unique conditions of these ecosystems, reports on their bacterial diversity are still fragmentary. From this perspective, 60 samples from 14 localities were analyzed. These localities were distributed in coastal sites with differently developed biological soil crusts, inner sites in the McMurdo Dry Valleys with soils lacking of plant coverage, and a site called Icarus Camp, with a crust developed on a thin locally weathered substrate of the underlying parent granitic-rock. Bacterial diversity was studied through 16S rRNA metabarcoding sequencing. Communities diversity, composition and the abundance and composition of different taxonomic groups were correlated to soil physicochemical characteristics. Firmicutes, Bacteroidetes, Cyanobacteria and Proteobacteria dominated these communities. Most phyla were mainly driven by soil granulometry, an often disregarded parameter and other abiotic parameters. Bacterial composition differed greatly among the three macrohabitats, each having a distinct bacterial profile. Communities within the two main habitats (coastal and inner ones) were well differentiated from each other as well, therefore depending on site-specific physicochemical characteristics. A core community of the whole samples was observed, mainly represented by Firmicutes and Bacteroidetes. Abstract : This study characterizes the diversity and composition of highly adapted soil bacterial communities in three distinct ice-free environments of Victoria Land, in Antarctica, in relation to different physicochemical edaphic parameters.